2014
DOI: 10.1007/s11596-014-1367-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen-related receptor alpha (ERRα) on proliferation and metastasis of human lung cancer A549 cells

Abstract: Estrogen-related receptor alpha (ERRα) plays an important role in the development of hormone-dependent cancers, but its roles in lung cancer remain elusive. The present study was aimed to investigate the effects of ERRα on the proliferation and metastasis of lung cancer A549 cells. The mRNA and protein levels of ERRα were detected in lung cancer A549 and MCF-7 cells and bronchial epithelial BEAS-2B cells by qRT-PCR and Western blotting, respectively. ERRα plasmid transfection and XCT-790 (an inverse agonist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
(45 reference statements)
3
27
0
Order By: Relevance
“…Invasion and metastasis are important clinicopathological factors for patients with CRC with unfavorable prognosis, and they are induced by EMT at the molecular level (26). Previous studies have reported that ERRα promotes invasion and metastasis by inducing EMT in lung cancer, and ovarian cancer cells (16,27). Therefore, we hypothesize that EMT mediated by ERRα underlies the mechanism for the association between high ERRα expression and poor prognosis in patients with CRC.…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 74%
See 3 more Smart Citations
“…Invasion and metastasis are important clinicopathological factors for patients with CRC with unfavorable prognosis, and they are induced by EMT at the molecular level (26). Previous studies have reported that ERRα promotes invasion and metastasis by inducing EMT in lung cancer, and ovarian cancer cells (16,27). Therefore, we hypothesize that EMT mediated by ERRα underlies the mechanism for the association between high ERRα expression and poor prognosis in patients with CRC.…”
Section: Errα Expression (N=128) ------------------------------------mentioning
confidence: 74%
“…Cancer cells demonstrate high proliferating capabilities and require constant biosynthesis of macromolecules as building blocks for the generation of new cells, thereby resulting in a high-energy demand for cancer cells (14). ERRα demonstrates key regulatory roles in a variety of malignant processes, including proliferation, invasion, metastasis and chemotherapy resistance (15)(16)(17). Since ERRα serves a crucial role in cancer initiation, development and progression, it may be speculated that ERRα holds significant clinical significance for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ERRα suppression results in EMT inhibition in breast cancer cells [23]. Metastasis, proliferation, and migration of A549 lung cancer cells were increased when ERRα overexpression [24]. We speculate that cordycepin inhibits mitochondrial activity and EMT in OVCAR-3 cells may due to ERRα regulation.…”
Section: Resultsmentioning
confidence: 99%